(untitled) (Research, Society and Development, 2022)
The practice of motor activities such as games, sports and plays in childhood has been defended as an important factor that can influence the level of physical activity in adulthood. The objective of the study was to verify associations between physical activity in childhood, perception of sports competition and practice of physical activity in adult. I used questions to assess physical activity in childhood and adult life and on the subscale of sports competence of the Physical Self-Perception Profile. It was observed that there was a correlation between physical activity in childhood and current physical activity only for the male sex (ró = 0,435, p = 0,009). We do not have significant association between self-perceived sports competition and physical activity in adult life. In the absence of association between sports competition and physical activity in adult life, it can be attributed to the characteristics of physical activities practiced in adult life, which are differentiated from those that encompass or construct sports competition. It is concluded that the engagement in the practice of physical activity may be associated with different components of the physical domain and not just to sports competence, because it is a multifactorial phenomenon that involves complexity.